2004
DOI: 10.1108/00035590410541364
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazole‐2‐tione and benzoxazole‐2‐tione derivatives as corrosion inhibitors for aluminium in hydrochloric acid

Abstract: The effect of benzimidazole‐2‐tione and benzoxazole‐2‐tione derivatives on the corrosion of aluminium in 0.1 M HCl has been investigated by a potentiostatic polarisation technique. Inhibition efficiencies were found to follow the order: benzimidazole‐2‐tione > 5‐methyl benzimidazole‐2‐tione > 5‐chloro benzimidazole‐2‐tione, while that of benzoxazole‐2‐tione derivatives were found to follow the order: 5‐methyl benzoxazole‐2‐tione > benzoxazole‐2‐tione > 5‐chloro benzoxazole‐2‐tione > 5‐nitro benzoxazole‐2‐tione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…To prevent the attack of the corrosive species on the metallic surface, it is very important to add a corrosion inhibitor to decrease the rate of metal dissolution in such solutions. Thus, many studies concerning the inhibition of carbon steel corrosion using corrosion inhibitors of nonionic surfactants are conducted in the medium [9][10][11][12][13]. Corrosion inhibitors can be divided into three kinds: (i) inorganic inhibitors, (ii) organic inhibitors and (iii) mixed material inhibitors [14].…”
Section: Introductionmentioning
confidence: 99%
“…To prevent the attack of the corrosive species on the metallic surface, it is very important to add a corrosion inhibitor to decrease the rate of metal dissolution in such solutions. Thus, many studies concerning the inhibition of carbon steel corrosion using corrosion inhibitors of nonionic surfactants are conducted in the medium [9][10][11][12][13]. Corrosion inhibitors can be divided into three kinds: (i) inorganic inhibitors, (ii) organic inhibitors and (iii) mixed material inhibitors [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that nitrogen-containing compounds such as azole derivatives [3][4][5][6][7], imidazolin derivatives [8,9], alkyl and aryl amines [10][11][12] perform better in hydrochloric acid. In general, most of the effective and efficient inhibitors in usage are organic compounds having π bonds and heteroatoms like nitrogen, sulphur and oxygen atoms, etc., in their structures [13].…”
Section: Introductionmentioning
confidence: 99%
“…Bereket et al 89 synthesised seven benzimidazole-2-tione and benzoxazole-2-tione derivatives, i.e. benzoxazole-2-tione (BOZ), benzimidazole-2-tione (BNZ), 5-methyl benzoxazole-2-tione (CH 3 -BOZ), 5methyl-benzimidazole-2-tione (CH 3 -BNZ), 5-chloro benzoxazole-2-tione (Cl-BOZ), 5-chloro-benzimidazole-2-tione (Cl-BNZ), and 5-nitro benzoxazole-2-tione (NO 2 -BOZ), and tested them as corrosion inhibitors for 99% aluminium in 0.1 M HCl solution at 20-60 °C, using the PSP technique.…”
Section: Organic Corrosion Inhibitors In Hcl Solutionmentioning
confidence: 99%